2007
DOI: 10.5194/acp-7-4661-2007
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric OH and Cl levels deduced from non-methane hydrocarbon measurements in a marine site

Abstract: Abstract. In situ continuous hourly measurements of C 2 -C 8 non-methane hydrocarbons (NMHC S ) have been performed from March to October 2006 at two coastal locations (natural and rural) on the island of Crete, in the Eastern Mediterranean. Well defined diel variations were observed for several short lived NMHC S (including ethene, propene, n-butane, n-pentane, n-hexane, 2-methyl-pentane). The daytime concentration of hydroxyl (OH) radicals estimated from these experimental data varied from 1.3×10 6 to ∼4.0×1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 59 publications
1
23
0
Order By: Relevance
“…A recent study reported similar Cl concentrations in the marine boundary layer (e.g. Arsene et al, 2007). Including Cl chemistry at those levels leads to a decrease of 4‰ in the isotopic composition of the H 2 reservoir whereas the contribution of O 1 D oxidation was found to be negligible.…”
Section: And O 1 D Chemistrymentioning
confidence: 58%
“…A recent study reported similar Cl concentrations in the marine boundary layer (e.g. Arsene et al, 2007). Including Cl chemistry at those levels leads to a decrease of 4‰ in the isotopic composition of the H 2 reservoir whereas the contribution of O 1 D oxidation was found to be negligible.…”
Section: And O 1 D Chemistrymentioning
confidence: 58%
“…Apart from the main sampling site at Finokalia, wet deposition samples were also collected at a secondary station situated at the University of Crete, 6 km south of Heraklion (35°20′N, 25°07′E). Further description of the site and the prevailing meteorology can be found in Arsene et al (2007). The sediment traps were moored for seven years (1999)(2000)(2001)(2002)(2003)(2004)(2005) in the southern Cretan Sea (along 45°06′E, 500 m and 1715 m depth, Kouvarakis et al, 2001).…”
Section: Sampling Sitementioning
confidence: 99%
“…While Cl-atoms have not been directly observed, labile sources in addition to ClNO 2 , such as Cl 2 , have been observed (Spicer et al, 1998). Regionally averaged Cl abundances have been inferred from observational analyses of hydrocarbons (Arsene et al, 2007;Cavender et al, 2008), but due to the limited spatial and temporal coverage of such measurements, the global Cl-atom source term remains largely unconstrained (Platt et al, 2004). Second, since ClNO 2 is not a terminal NO x sink, production via N 2 O 5 heterogeneous reaction represents a reduction, by as much as 50%, in the amount of NO x removed during night by NO 3 and N 2 O 5 chemistry, effectively enhancing the NO x -lifetime because Reaction (R8) ultimately returns one NO x .…”
Section: Introductionmentioning
confidence: 99%